Bondi Cave and the Middle-Upper Palaeolithic transition in western Georgia (south Caucasus). (15th August 2016) - Pleurdeau, David; Moncel, Marie-Hélène; Pinhasi, Ron; Yeshurun, Reuven; Higham, Tom; Agapishvili, Tamar; Bokeria, Maka; Muskhelishvili, Alexander; Le Bourdonnec, François-Xavier; Nomade, Sébastien; Poupeau, Gérard; Bocherens, Hervé; et al.
Abstract: The late Pleistocene expansion of anatomically modern humans (AMHs) into Eurasia and the concurrent demise of the Neanderthals appears to be a complex and regionally variable process. The southern Caucasus region, with its rich cave-sites, has recently provided important results regarding this process. In this paper we report on the results of fieldwork in Bondi Cave, Western Georgia, providing a new radiocarbon chronology, stratigraphic observations, analyses of lithic technology and provenance, faunal and floral remains as well as paleoenvironmental data. The cave includes Middle Palaeolithic (ca, 45, 000 ka cal. BP) cultural horizons and a long Upper Palaeolithic sequence (ca. 40, 000–27, 000 cal. BP from layer V to IV). A modern human tooth was found in layer Vb. We estimate its age at 39, 000–35, 800 Cal BP (95.4%), based on the Bayesian age model we built. If the context of the tooth is reliable, as we think it is, this would make it the oldest morphologically modern human in the Caucasus. Upper Palaeolithic hunting of tur and bison, as well as the collection of various plants including flax is attested. Mobile Upper Palaeolithic foragers inhabited the cave in generally cold and dry periods, but a mosaic of environments, including forests and meadows, was nonetheless available to them. The archaeological sequence of Bondi and adjacent sites indicates a substantial time gap between the Middle and Upper Palaeolithic occupations, thus disproving Neanderthal-AMH interaction in this area and lending support to a replacement scenario in the southern Caucasus, assuming of course that the Early Upper Palaeolithic (EUP) is related to the arrival of AMHs. Highlights: Bondi Cave contains an archaeological sequence of more than 3 m in thickness, with Middle/Upper Palaeolithic occupations from ∼50 ka. The site offers a key-window to question the continuity/rupture in human population during MP/UP transition in Caucasus. The paper is a multidisciplinary synthesis including the sequence in the chronological and palaeoenvironmental context of the region.